Instructional Format and Differences in Remedial Mathematics Performance for Community College Students: A Multiyear Investigation (Global Journal of Human-Social Science, 2017)
Differences in student success rates in remedial mathematics courses as a function of the instructional format (i.e., traditional face-to-face and computer-assisted) were investigated in this study. Data from the 2012-2013 through the 2014-2015 academic years from a single Texas community college were analyzed. For the 3 academic years examined, statistically significant differences were present in remedial mathematics performance by instructional format, with trivial to small effect sizes. Students had higher success rates in remedial mathematics courses in which a traditional lecture format was used than in computer-assisted courses. Implications and recommendations for future research were discussed.
Keywords: Differences in student success rates in remedial mathematics courses as a function of the instructional format (ie; traditional face-to-face and com